Erratum - Cardoso, Mateus Ettori; Costa, Álvaro Furtado da; Binelli, Claudia Afonso; Carvalhal, Layana Guedes; Silva, Roberto José Carvalho da; Nogueira, Roberta Schiavon (Brazilian Journal of Sexually Transmitted Diseases, 2023)
***